"Gente da terra e das águas" : avaliação da pesca e dos resíduos de Mytella spp. pelas marisqueiras da Taiçoca de Fora - Nossa Senhora do Socorro/SE - Alves, Analee Cruz (2016)
The local fisheries of sutinga (Mytella charruana) and sururu (Mytella guyanensis) has a great importance for the Taiçoca de Fora community, located in the municipality of Nossa Senhora do Socorro-SE, where families survive on fishing and shellfish. However, the solid waste generated by this activity doesn’t have appropriate allocation, the shells of Mytella spp., rich sources of calcium carbonate (CaCO3) are found in abundance at the Cajaíba river shores. This study’s aim was to assess the current situation of fishing and improper disposal of solid waste from Mytella spp. in the Taiçoca de Fora. This research has methodical qualitative and quantitative perspective, guided by deductive empirical approach, with semi-structured interviews applied to 38 fishermen and shellfish gatherers, and 3 managers of the main relevant bodies; Cartographic identification of main waste disposal point and natural stocks of species extraction; Habitability index analysis and the processing system resource in the village; Bio-ecological aspects of species have been investigated to understand the animal's life cycle and the possible use of the residual, considering the socioeconomic, cultural and environmental aspects of the region. The results revealed that in different times may be captured between 2-8kg of shellfish in lean state, and 4-16kg in fatty state; Maps were drawn indicating the main waste disposal point of residue and the main fishing spots in activity in the Cajaíba river; Daily can be produced until 3kg of residue by a tin of Mytella spp caught; The current models of sewage and solid residue collect don’t attend the community in an efficient and satisfactory manner. The information produced contributed to the existing theoretical and methodological gap under the theme, the same were delivered to community through a workshop and of the booklet safe and healthy work. It is the latent need for a fishery management plan and sustainable management so that there is rational resource extraction and management of fishery residue, but that this will occur should be considered in the forefront the social and environmental needs.